2019
DOI: 10.1007/s40093-019-0270-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of physicochemical changes during composting rice straw with chicken and donkey manure

Abstract: Purpose Traditional methods of composting are limited in timely production of good-quality compost due to recalcitrant nature of materials of plant origin. This study focused on evaluating the use chicken and donkey manure as starter cultures to biostimulate bioconversion of rice straw into bioorganic fertilizer. Use of starter cultures would enhance composting as a strategy for rice straw management to enhance soil fertilization and reduce environmental pollution. Methods In this study, chicken manure and don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 39 publications
3
16
1
2
Order By: Relevance
“…The manure was reported to improve the soil quality by reducing the occurrence of crop parasites in the soil and reducing the acidity levels in rice fields. Karanja et al [26] had previously reported that donkey manure significantly improved the composting process and the quality of the resultant compost for use as manure in crop fields. Manure yield could be increased through accumulation enabled by enclosing or housing of donkeys to increase the concentration of dung [27].…”
Section: Discussionmentioning
confidence: 99%
“…The manure was reported to improve the soil quality by reducing the occurrence of crop parasites in the soil and reducing the acidity levels in rice fields. Karanja et al [26] had previously reported that donkey manure significantly improved the composting process and the quality of the resultant compost for use as manure in crop fields. Manure yield could be increased through accumulation enabled by enclosing or housing of donkeys to increase the concentration of dung [27].…”
Section: Discussionmentioning
confidence: 99%
“…The composition of microbial communities during composting is dependent on the constant change in the physicochemical parameters such as temperature, moisture, C/N ratio, oxygen rate and pH [75,76]. The role of the microbial community in the degradation of organic matter, proteins, lipids, cellulose and lignin during composting has been highlighted in several studies as well [77].…”
Section: Compost Microbial Community Structure Profiling Techniquesmentioning
confidence: 99%
“…Duration of Composting and Changes in Temperature, pH and C/N Ratio during Composting: A Review Composting of Chinese medicinal herbal residue mixed with food waste and saw dust using aerated reactor was complete within a period of 60 days (Zhou et al, 2014). Rice straw mixed separately with chicken manure and donkey manure using aerated bags complete composting within 62 days (Karanja et al, 2019). Composting of municipal sewage sludge in the form of solid cake and partially dried to 80-85% carried out using bioreactor was complete within a period of 45 days (Dzulkurian et al, 2017).…”
Section: Aerobic Compostingmentioning
confidence: 99%